Propafenone in restoring sinus rhythm among patients with persistent atrial fibrillation. PROMETEY – an open, multicenter, pilot study performed in the Russian Federation - I. G. Fomina (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study efficacy and safety of propafenone (loading single dose of 600 mg per os) in treating atrial fibrillation (AF) paroxysms. Material and methods. The study included 233 patients with persistent AF, aged 31-62 (mean age 57.6 ± 2.8 years), from 10 Russian regions. For AF paroxysm treatment, all patients received propafenone (600 mg per os). Results. Propafenone restored sinus rhythm in 196 patients (84%). Mean time to restoring sinus rhythm was 220 ± 60 minutes. In the first 4 hours, anti-AF effect of propafenone was observed in 150 participants (64%). Adverse events were registered in 15 patients (6%): intraventricular block - in 7 individuals (3%), Stage II atrio-ventricular block – in 6 (3%), dyspepsia – in 2 patients (0.9%). Blood pressure drop to 100/70 mm Hg was observed in 24 cases (10%). Adverse effects disappeared without any additional therapy. Conclusion. Propafenone therapy (600 mg per os) effectively and safely restored sinus rhythm in 84% of the patients with persistent AF. The mean time of sinus rhythm conversion was 220 ± 60 minutes; in the first 4 hours, sinus rhythm was restored in 64% of the patients.